KADAR KADMIUM PADA AIR SUMUR GALI DISEKITAR TEMPAT PEMROSESAN AKHIR SAMPAH (STUDI DI TEMPAT PEMROSESAN AKHIR SAMPAH X KABUPATEN JEMBER, INDONESIA) - Lailatul Qadriyah; Anita Dewi Moelyaningrum; Prehatin Trirahayu Ningrum (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2019)
The controlled landfill method can produce leachate water. Leachate water has high potential to contaminate ground water. The cadmium (Cd) can spread into the soil through a process of impregnation that follows the movement of groundwater flow. The purpose of this study was to analyze the relationship between the distance and well construction with cadmium content in the well water dug around the landfill. This research was an observational analytic research with cross sectional research design. The data collection method used in this research were observation, measurement, documentation and laboratory test. The result of laboratory test showed 80% of the wells exceed the quality standard (0,005 ppm). The result of bivariate analysis using chi square test showed that there was no correlation between the distance with cadmium content in dug well water around landfill (sig = 0.173) and there was a relation between well construction with cadmium content in dug well water around landfill (sig = 0.035). The good standart construction of dug well can inhibit the cadmium in the dug well water.